Conductive carbon paste, preparation method thereof and perovskite solar cell module
Patent Information
- Application Number
- CN202610939923.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-10-09
AI Technical Summary
然而,现有树脂体系(比如,单一的聚苯乙烯或PVDF)缺乏弹性释放机制,且干燥工艺控制不当,导致大面积刮涂的碳膜极易产生“泥裂(Mud-cracking)”现象,此外,碳膜与钙钛矿层界面的物理粘附力极弱,极易剥离脱落
[0018]依据上述实施例的导电碳浆及其制备方法、钙钛矿太阳能电池模组,本申请导电碳浆中的正交非极性溶剂可以避免传统碳浆直接涂覆于裸露的钙钛矿光吸收层上损坏钙钛矿晶格的风险,从而确保钙钛矿光吸收层的完整性;热塑性粘结剂中的极性酯基的聚合物提供了与底材的强极性附着力,非结晶型聚烯烃弹性体提供了高弹性的应力缓冲网络以消除碳浆层开裂,同时赋予了顶电极层极低的水汽透过率能力,实现了对钙钛矿太阳能电池模组的原位阻水封装;无机p型半导体功能微粉可以均匀锚固于碳导电填料的碳网络体系中,即在顶电极层内部构筑三维体相空穴提取网络,相比于传统二维平面的独立空穴层,这种三维体相空穴提取网络极大缩短了电荷传输距离,显著降低了接触电阻,大幅提升了无空穴层电池的开路电压和填充因子,即极大提升了碳/钙钛矿界面的电荷分离效率,从而能够完全省去传统电池结构中昂贵且易降解的独立空穴传输层。本申请的导电碳浆可直接涂覆于钙钛矿光吸收层表面,实现了空穴提取与电荷收集的一体化,大幅简化了无空穴层钙钛矿模组的器件结构与制备工艺,极具规模化量产前景。
Smart Images

Figure CN122889482A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solar cell materials and optoelectronic device fabrication technology, specifically to a conductive carbon paste and its preparation method, and a perovskite solar cell module. Background Technology
[0002] Organic-inorganic hybrid perovskite solar cells (PSCs) have attracted much attention due to their excellent photoelectric conversion efficiency and low-cost manufacturing potential. However, traditional high-efficiency PSCs typically require the use of expensive organic hole transport materials (such as Spiro-OMeTAD or PTAA) and noble metal electrodes (such as gold and silver), which greatly increases the manufacturing cost. Furthermore, the organic hole layer and metal electrodes are highly susceptible to inducing ion migration, resulting in poor long-term device stability.
[0003] To promote the commercialization of perovskite modules, replacing noble metal electrodes and hole transport layers with low-cost, chemically stable carbon electrodes to construct hole-layer-free perovskite solar cells (HTL-free PSCs) has become an important research and development direction in the industry. However, existing direct-coating low-temperature carbon pastes face the following serious technical bottlenecks in practical applications: Substrate damage (poor orthogonality): Traditional commercially available carbon pastes (such as those used in lithium batteries or traditional printing industries) often use polar solvents (such as NMP, DMF, ethers, etc.). These solvents can severely dissolve or damage the extremely fragile perovskite lattice at the moment of coating, leading to perovskite degradation and failure.
[0004] Coating cracking and poor adhesion: The carbon layer undergoes significant volume shrinkage during the drying and curing process. However, existing resin systems (such as single polystyrene or PVDF) lack an elastic release mechanism, and improper drying process control makes large-area coated carbon films prone to "mud-cracking." In addition, the physical adhesion between the carbon film and the perovskite layer is extremely weak, making it very easy to peel off.
[0005] Low hole extraction efficiency: When pure carbon materials come into direct contact with perovskite, there is a large potential barrier at the interface, resulting in low hole extraction and transport efficiency of the device.
[0006] Therefore, how to develop a conductive carbon paste that improves the hole extraction capability and transmission efficiency of devices is an urgent technical problem to be solved. Summary of the Invention
[0007] The main technical problem solved by this invention is to develop a conductive carbon paste that can improve the hole extraction capability and transmission efficiency of devices.
[0008] According to a first aspect, one embodiment provides a conductive carbon paste, comprising: an orthogonal nonpolar solvent, a thermoplastic binder, a carbon conductive filler, and an inorganic p-type semiconductor functional micro powder.
[0009] In one embodiment, the thermoplastic binder accounts for 10% to 50% of the total solids content of the conductive carbon paste; the carbon conductive filler accounts for 50% to 90% of the total solids content of the conductive carbon paste.
[0010] In one embodiment, the orthogonal nonpolar solvent includes a low-boiling-point solvent and a high-boiling-point solvent; the low-boiling-point solvent includes at least one of ethyl acetate, methyl acetate, propyl acetate, and naphtha; the high-boiling-point solvent includes at least one of chlorobenzene, toluene, xylene, anisole, terpineol, isooctyl alcohol, aromatic 150, aromatic 100, propylene glycol methyl ether acetate, dipropylene glycol monomethyl ether, diacetone alcohol, ethylene glycol ethyl ether acetate, diethylene glycol ethyl ether acetate, and propylene glycol methyl ether acetate.
[0011] In one embodiment, the thermoplastic binder comprises: a polar ester-based polymer and an amorphous polyolefin elastomer; the mass ratio of the polar ester-based polymer to the amorphous polyolefin elastomer is 5:1 to 9:1; the polar ester-based polymer includes polymethyl methacrylate; and the amorphous polyolefin elastomer includes polyisobutylene and / or styrene block copolymers.
[0012] In one embodiment, the carbon conductive filler includes: micron-sized flake graphite, nano-sized conductive carbon black, nano-sized Ketjen black, and one-dimensional carbon nanotubes; the carbon conductive filler is composed of micron-sized flake graphite, nano-sized conductive carbon black, and one-dimensional carbon nanotubes; the micron-sized flake graphite accounts for 50% to 80% of the total weight of the carbon conductive filler, the nano-sized conductive carbon black accounts for 10% to 40% of the total weight of the carbon conductive filler, the nano-sized Ketjen black accounts for 5% to 10% of the total weight of the carbon conductive filler, and the one-dimensional carbon nanotubes account for 5% to 10% of the total weight of the carbon conductive filler.
[0013] In one embodiment, the inorganic p-type semiconductor functional micro powder includes at least one of cuprous thiocyanate, nickel oxide, molybdenum disulfide, tungsten disulfide, cuprous oxide, cuprous iodide, and molybdenum oxide micro powder; the average particle size of the inorganic p-type semiconductor functional micro powder is between 10 nm and 500 nm; the inorganic p-type semiconductor functional micro powder accounts for 0.5% to 20% of the total weight of the carbon conductive filler.
[0014] According to a second aspect, one embodiment provides a method for preparing a conductive carbon paste, the method comprising: A thermoplastic adhesive is dissolved in an orthogonal nonpolar solvent to obtain a polymeric adhesive solution. Carbon conductive filler, inorganic p-type semiconductor functional micro powder and the polymer adhesive are mixed to fully wet and coat the solid powder to obtain a coarse slurry. The coarse slurry is sheared and ground to uniformly anchor the inorganic p-type semiconductor functional micro powder in situ within the carbon network system of the carbon conductive filler, thereby obtaining the conductive carbon slurry.
[0015] In one embodiment, the fineness of the conductive carbon paste is less than or equal to 15 μm.
[0016] According to a third aspect, one embodiment provides a perovskite solar cell module, comprising: Conductive substrate; An electron transport layer is stacked on the conductive substrate; A perovskite light-absorbing layer is stacked on the electron transport layer; A top electrode layer is stacked on the perovskite light-absorbing layer.
[0017] In one embodiment, the top electrode layer is formed by coating the exposed perovskite light-absorbing layer with conductive carbon paste, and then drying and curing at low temperature to form a three-dimensional bulk hole extraction network.
[0018] Based on the conductive carbon paste and its preparation method described in the above embodiments, and the perovskite solar cell module, the orthogonal nonpolar solvent in the conductive carbon paste of this application can avoid the risk of damaging the perovskite lattice by directly coating the exposed perovskite light-absorbing layer with traditional carbon paste, thereby ensuring the integrity of the perovskite light-absorbing layer; the polar ester polymer in the thermoplastic binder provides strong polar adhesion to the substrate, and the non-crystalline polyolefin elastomer provides a highly elastic stress buffer network to eliminate cracking of the carbon paste layer, while giving the top electrode layer extremely low water vapor transmittance, thus realizing the perovskite solar cell module. This invention relates to in-situ water-blocking encapsulation of battery modules. Inorganic p-type semiconductor functional microparticles can be uniformly anchored within a carbon network system of conductive carbon fillers, constructing a three-dimensional bulk hole extraction network within the top electrode layer. Compared to traditional two-dimensional planar independent hole layers, this three-dimensional bulk hole extraction network significantly shortens the charge transport distance, substantially reduces contact resistance, and greatly improves the open-circuit voltage and fill factor of hole-free batteries. This significantly enhances the charge separation efficiency at the carbon / perovskite interface, thus completely eliminating the expensive and easily degradable independent hole transport layer found in traditional battery structures. The conductive carbon paste of this application can be directly coated onto the surface of the perovskite light-absorbing layer, achieving integrated hole extraction and charge collection. This greatly simplifies the device structure and fabrication process of hole-free perovskite modules, demonstrating significant potential for large-scale mass production. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of a conductive carbon paste according to one embodiment; Figure 2This is a schematic flowchart of a method for preparing conductive carbon paste according to one embodiment; Figure 3 This is a schematic diagram of the structure of a perovskite solar cell module according to one embodiment; Figure 4 This is a scanning electron microscope image of the top electrode of the perovskite solar cell module in Experiment 2; Figure 5 This is a voltage-current diagram after the photoelectric performance test of the perovskite solar cell module in Experiment 1. Figure 6 This is a voltage-current diagram after the photoelectric performance test of the perovskite solar cell module in Experiment 2. Figure 7 This is a voltage-current diagram after the photoelectric performance test of the perovskite solar cell module in control experiment 1. Detailed Implementation
[0020] The present invention will now be described in further detail with reference to specific embodiments and accompanying drawings. Similar elements in different embodiments are referred to by associated similar element reference numerals. In the following embodiments, many details are described to facilitate a better understanding of the invention. However, those skilled in the art will readily recognize that some features may be omitted in different situations, or may be replaced by other elements, materials, or methods. In some cases, certain operations related to the present invention are not shown or described in the specification. This is to avoid obscuring the core parts of the invention with excessive description. For those skilled in the art, detailed description of these related operations is not necessary; they can fully understand the related operations based on the description in the specification and general technical knowledge in the art.
[0021] Furthermore, the features, operations, or characteristics described in the specification can be combined in any suitable manner to form various embodiments. At the same time, the steps or actions in the method description can be rearranged or adjusted in a manner obvious to those skilled in the art. Therefore, the various orders in the specification and drawings are only for the clear description of a particular embodiment and do not imply a necessary order, unless otherwise stated that a particular order must be followed.
[0022] The serial numbers assigned to components in this article, such as "first" and "second", are used only to distinguish the objects being described and have no sequential or technical meaning.
[0023] Perovskite solar cells are considered one of the most promising next-generation photovoltaic technologies due to their advantages such as high photoelectric conversion efficiency, low material cost, solution-processability, and low-temperature fabrication. In recent years, with continuous progress in material system optimization, interface engineering, and device structure design, the efficiency of small-area perovskite solar cells has exceeded 26%, and significant breakthroughs have also been achieved in the efficiency of large-area modules, demonstrating promising prospects for industrial application. However, compared with efficiency improvements, perovskite solar cell modules still have significant shortcomings in long-term operational stability and service life, becoming a key bottleneck restricting their large-scale application and commercialization.
[0024] Under practical operating conditions, perovskite solar cell modules typically rely on expensive organic hole transport materials and noble metal electrodes to achieve high output voltage and power. However, due to factors such as the easy degradation of organic transport materials, the susceptibility of noble metals to ion migration, and environmental aging, the interfaces of each sub-cell inevitably degrade. Furthermore, during the fabrication and application process, the module is also affected by complex factors such as cost pressures, process complexity, and encapsulation water-proofing requirements, leading to a significant decrease in the long-term stability of sub-cells using noble metal electrodes. Replacing noble metals and the hole layer with low-cost carbon-based materials is an ideal solution.
[0025] However, traditional carbon electrodes often suffer from work function mismatch, requiring an external, independent organic hole transport layer to address charge recombination. This necessitates complex, multi-step fabrication and expensive materials. For fully thin-film, monolithically integrated perovskite devices without a hole layer, the additional hole layer not only increases interfacial resistance but also makes the heat-sensitive perovskite layer highly susceptible to irreversible damage during high-temperature or multi-step solvent processing.
[0026] Based on this, this application proposes a conductive carbon paste comprising an orthogonal nonpolar solvent, a thermoplastic binder, a carbon conductive filler, and inorganic p-type semiconductor functional micro powder. Orthogonal nonpolar solvents can avoid the risk of damaging the perovskite lattice by directly coating the exposed perovskite light-absorbing layer with traditional carbon paste, thus ensuring the integrity of the perovskite light-absorbing layer. The polar ester polymer in the thermoplastic binder provides strong polar adhesion to the substrate, and the non-crystalline polyolefin elastomer provides a highly elastic stress buffer network to eliminate cracking of the carbon paste layer, while giving the top electrode layer extremely low water vapor transmission capacity, realizing in-situ water-blocking encapsulation of the perovskite solar cell module. Inorganic p-type semiconductor functional micropowders can be uniformly anchored in the carbon network system of carbon conductive filler, that is, a three-dimensional bulk hole extraction network is constructed inside the top electrode layer. Compared with the traditional two-dimensional planar independent hole layer, this three-dimensional bulk hole extraction network greatly shortens the charge transport distance, significantly reduces the contact resistance, and greatly improves the open circuit voltage and fill factor of the hole-free cell, that is, greatly improves the charge separation efficiency of the carbon / perovskite interface, thus completely eliminating the expensive and easily degradable independent hole transport layer in the traditional cell structure. The conductive carbon paste of this application can be directly coated on the surface of the perovskite light absorption layer, realizing the integration of hole extraction and charge collection, which greatly simplifies the device structure and fabrication process of perovskite modules without hole layers, and has great potential for large-scale mass production.
[0027] The following is a detailed description of conductive carbon paste.
[0028] Please see Figure 1 , Figure 1 This is a schematic diagram of a conductive carbon paste according to one embodiment. Figure 1 As shown, the conductive carbon paste of this application includes n kinds of orthogonal nonpolar solvents, m kinds of thermoplastic binders, x kinds of carbon conductive fillers and y kinds of inorganic p-type semiconductor functional micro powders, wherein n, m, x and y are all integers not less than 1.
[0029] In some embodiments, the thermoplastic binder accounts for 10% to 50% of the total solids content of the conductive carbon paste; the carbon conductive filler accounts for 50% to 90% of the total solids content of the conductive carbon paste.
[0030] In practical applications, the thermoplastic binder can account for 10%, 40%, or 50% of the total solids content of the conductive carbon paste; the carbon conductive filler can account for 50%, 60%, or 90% of the total solids content of the conductive carbon paste.
[0031] Of course, the proportion of thermoplastic binder in the total solid content of conductive carbon paste can be any value between 10% and 50%; the proportion of carbon conductive filler in the total solid content of conductive carbon paste can also be any value between 50% and 90%; and the sum of the proportions of these two components in the total solid content of conductive carbon paste is 100%.
[0032] In some embodiments, the orthogonal nonpolar solvent includes low-boiling-point solvents and high-boiling-point solvents. Low-boiling-point solvents include at least one of ethyl acetate, methyl acetate, propyl acetate, and naphtha; high-boiling-point solvents include at least one of chlorobenzene, toluene, xylene, anisole, terpineol, isooctanol, aromatic 150, aromatic 100, propylene glycol methyl ether acetate, dipropylene glycol monomethyl ether, diacetone alcohol, ethylene glycol ethyl ether acetate, diethylene glycol ethyl ether acetate, and propylene glycol methyl ether acetate.
[0033] It should be noted that low-boiling-point solvents account for 10%-30% of the total volume of orthogonal nonpolar solvents; high-boiling-point solvents account for 70%-90% of the total volume of orthogonal nonpolar solvents. In other words, low-boiling-point solvents can account for 10%, 20%, or 30% of the total volume of orthogonal nonpolar solvents; high-boiling-point solvents can account for 70%, 80%, or 90% of the total volume of orthogonal nonpolar solvents.
[0034] It should be noted that after the conductive carbon paste is printed onto the exposed perovskite light-absorbing layer, the low-boiling-point solvent evaporates rapidly, accelerating film setting. Furthermore, the shrinkage stress generated by this rapid evaporation promotes close contact between the conductive particles of the carbon conductive filler, reducing the electrode film resistance. Simultaneously, the rapid removal of the low-boiling-point solvent helps lower the curing temperature, preventing thermal damage to the perovskite layer. The high-boiling-point solvent evaporates slowly and at a controlled rate, allowing sufficient leveling time for the coating paste during drying, effectively suppressing the "coffee ring" effect and pinhole defects, ensuring uniform film thickness and no pores, and also improving the interfacial adhesion between the carbon electrode layer and its underlying functional layer. In addition, the slow-evaporation characteristic of the high-boiling-point solvent gives the conductive carbon paste better storage stability, preventing it from drying and deteriorating during storage, thus extending its shelf life.
[0035] It should be noted that since the conductive carbon paste does not contain polar solvents that dissolve the perovskite lattice, directly coating the conductive carbon paste onto the exposed perovskite light-absorbing layer will not damage the perovskite lattice, thus ensuring the integrity of the perovskite light-absorbing layer.
[0036] In some embodiments, the thermoplastic binder includes: a polar ester-based polymer and an amorphous polyolefin elastomer; wherein the mass ratio of the polar ester-based polymer to the amorphous polyolefin elastomer is 5:1 to 9:1; the polar ester-based polymer includes polymethyl methacrylate; and the amorphous polyolefin elastomer includes polyisobutylene or styrene block copolymer.
[0037] In practical applications, thermoplastic adhesives can be obtained by mixing polymethyl methacrylate (PMMA) and polyisobutylene in a mass ratio of 5:1, 7:1, or 9:1. Of course, the mass ratio of PMMA to polyisobutylene can also be any ratio from 5:1 to 9:1.
[0038] In practical applications, thermoplastic adhesives can be obtained by mixing polymethyl methacrylate (PMMA) and styrene block copolymers in a mass ratio of 6:1, or by mixing PMMA and styrene block copolymers in a mass ratio of 8:1. Of course, the mass ratio of PMMA to styrene block copolymers can also be any ratio from 5:1 to 9:1.
[0039] In some embodiments, the carbon conductive filler includes: micron-sized flake graphite, nano-sized conductive carbon black, nano-sized Ketjen black, and one-dimensional carbon nanotubes; micron-sized flake graphite accounts for 50% to 80% of the total weight of the carbon conductive filler, nano-sized conductive carbon black accounts for 10% to 40% of the total weight of the carbon conductive filler, nano-sized Ketjen black accounts for 5% to 10% of the total weight of the carbon conductive filler, and one-dimensional carbon nanotubes account for 5% to 10% of the total weight of the carbon conductive filler.
[0040] In practical applications, micron-sized flake graphite accounts for 60% of the total weight of the carbon conductive filler, nano-sized conductive carbon black accounts for 30%, nano-sized Ketjen black accounts for 5%, and one-dimensional carbon nanotubes account for 5%. Of course, the percentage of micron-sized flake graphite in the total weight of the carbon conductive filler can be any value between 50% and 80%, the percentage of nano-sized conductive carbon black can be any value between 10% and 40%, the percentage of nano-sized Ketjen black can be any value between 5% and 10%, and the percentage of one-dimensional carbon nanotubes can be any value between 5% and 10%. Furthermore, the total percentage of these four components in the total weight of the carbon conductive filler is 100%.
[0041] In some embodiments, the inorganic p-type semiconductor functional micropowder includes at least one of cuprous thiocyanate, nickel oxide, molybdenum disulfide, tungsten disulfide, cuprous oxide, cuprous iodide, and molybdenum oxide micropowder; the average particle size of the inorganic p-type semiconductor functional micropowder is between 10 nm and 500 nm; the inorganic p-type semiconductor functional micropowder accounts for 0.5% to 20% of the total weight of the carbon conductive filler.
[0042] It should be noted that the inorganic p-type semiconductor functional micro powder can be any one of cuprous thiocyanate, nickel oxide, molybdenum disulfide, tungsten disulfide, cuprous oxide, cuprous iodide, and molybdenum oxide micro powder, or any two or more of them.
[0043] It should be noted that the inorganic p-type semiconductor functional micropowder can account for 0.5%, 3%, 5%, or 20% of the total weight of the carbon conductive filler. The average particle size of the inorganic p-type semiconductor functional micropowder can be any value between 10 nm and 500 nm. For example, the average particle size of the inorganic p-type semiconductor functional micropowder can be 10 nm, 50 nm, 100 nm, 160 nm, 230 nm, 350 nm, 420 nm, or 500 nm.
[0044] The orthogonal nonpolar solvent in the conductive carbon paste of this application avoids the risk of damaging the perovskite lattice when the traditional carbon paste is directly coated onto the exposed perovskite light-absorbing layer, thus ensuring the integrity of the perovskite light-absorbing layer. The polar ester polymer in the thermoplastic binder provides strong polar adhesion to the substrate, and the non-crystalline polyolefin elastomer provides a highly elastic stress buffer network to eliminate cracking of the carbon paste layer, while giving the top electrode layer extremely low water vapor transmission capacity, realizing in-situ water-blocking encapsulation of the perovskite solar cell module. The inorganic p-type semiconductor functional micropowder can be uniformly anchored in the carbon network system of the carbon conductive filler, that is, a three-dimensional bulk hole extraction network is constructed inside the top electrode layer. Compared with the traditional two-dimensional planar independent hole layer, this three-dimensional bulk hole extraction network greatly shortens the charge transmission distance, significantly reduces the contact resistance, and greatly improves the open circuit voltage and fill factor of the hole-free cell, that is, greatly improves the charge separation efficiency of the carbon / perovskite interface, thus completely eliminating the expensive and easily degradable independent hole transport layer in the traditional cell structure. The conductive carbon paste of this application can be directly coated on the surface of the perovskite light absorption layer, realizing the integration of hole extraction and charge collection, which greatly simplifies the device structure and fabrication process of perovskite modules without hole layers, and has great potential for large-scale mass production.
[0045] The following is a detailed description of the preparation method of conductive carbon paste.
[0046] Please see Figure 2 , Figure 2 This is a schematic flowchart illustrating a method for preparing conductive carbon paste according to one embodiment. Figure 2 As shown, the preparation method includes: S201. Dissolve the thermoplastic adhesive in an orthogonal nonpolar solvent to obtain a polymeric adhesive solution.
[0047] It should be noted that thermoplastic adhesives and orthogonal nonpolar solvents have been described in detail in the preceding sections and will not be repeated here.
[0048] In practical applications, the process of dissolving thermoplastic adhesives in orthogonal nonpolar solvents can be as follows: dissolve the thermoplastic adhesive in the orthogonal nonpolar solvent and heat and stir until the thermoplastic adhesive is completely dissolved in the orthogonal nonpolar solvent, thereby obtaining a polymeric adhesive solution.
[0049] S202. Mix carbon conductive filler, inorganic p-type semiconductor functional micro powder and polymer adhesive to fully wet and coat the solid powder to obtain a coarse slurry.
[0050] It should be noted that carbon conductive fillers and inorganic p-type semiconductor functional micro powders have been described in detail in the preceding sections and will not be repeated here.
[0051] In practical applications, the process of mixing carbon conductive filler, inorganic p-type semiconductor functional micro powder and polymer adhesive can be carried out by mixing the carbon conductive filler, inorganic p-type semiconductor functional micro powder and polymer adhesive and stirring until the surface of inorganic p-type semiconductor functional micro powder and the carbon powder voids of carbon conductive filler are wetted and coated by polymer adhesive, thereby obtaining a coarse slurry.
[0052] S203. The coarse slurry is sheared and ground to make the inorganic p-type semiconductor functional micro powder uniformly anchored in situ in the carbon network system of carbon conductive filler, so as to obtain conductive carbon slurry.
[0053] In practical applications, the process of shearing and grinding the coarse slurry can be carried out by using a three-roll mill to perform high-shear grinding on the coarse slurry, so that the inorganic p-type semiconductor functional micro powder is uniformly anchored in situ in the carbon network system of carbon conductive filler, thereby obtaining conductive carbon slurry.
[0054] It should be noted that after high-shear grinding of the coarse slurry, the various components interpenetrate or encapsulate each other through a high-shear dispersion structure to form a uniform conductive carbon slurry. In the conductive carbon slurry, each inorganic p-type semiconductor functional micropowder is tightly anchored to at least one carbon conductive filler carbon conductive particle, thereby forming a three-dimensional bulk hole extraction network.
[0055] In some embodiments, the fineness of the conductive carbon paste is less than or equal to 15 μm.
[0056] It should be noted that the fineness of the conductive carbon paste can be greater than 0 μm and less than or equal to 15 μm. For example, the fineness of the conductive carbon paste can be 15 μm, 12 μm, 10 μm, or 9 μm.
[0057] The following uses Control Experiment 1 and Experiments 1-5 for comparative explanation.
[0058] Experiment 1 Multiple tandem, hole-free perovskite solar cell units are integrated on a glass substrate. The structure of each cell unit, from bottom to top, consists of: a 100 nm thick ITO conductive glass substrate, a 50 nm thick SnO2 electron transport layer, an 800 nm thick FAPbI3 perovskite light-absorbing layer, and a 50 μm thick carbon electrode layer containing inorganic p-type dopant, i.e., the top electrode layer. The fabrication methods of each layer are as follows: (1) On a conductive substrate with a size of 60×60cm, the surface of the ITO conductive glass substrate is scribed with P1 to form 98 sub-electrode regions.
[0059] (2) Preparation of electron transport layer: SnO2 colloidal aqueous dispersion and deionized water are mixed in a ratio of 1:4 and stirred evenly; ITO conductive glass substrate is placed on the slit coater platform, and the distance between the coating head and the ITO conductive glass substrate is adjusted so that D11 = 0.15 mm. Tin oxide dispersion is coated on the ITO conductive glass substrate at a coating rate of V11 = 15 mm / s. After forming SnO2 liquid film, it is immediately transferred to the hot stage for annealing. The annealing temperature is F11 = 160℃ and the annealing time is T11 = 30 min to obtain SnO2 electron transport layer.
[0060] (3) Preparation of perovskite light absorption layer: FAI and PbI2 are dissolved in DMF solvent in stoichiometric ratio to prepare FAPbI3 perovskite solution; the substrate with electron transport layer coating is placed on the slit coater platform, the coating head gap D12 is set to 0.12 mm, the coating rate V12 is set to 10 mm / s, the FAPbI3 perovskite solution is injected and the slit coater platform is started to coat the FAPbI3 perovskite solution on the SnO2 electron transport layer. After forming a perovskite liquid film, it is immediately annealed on the hot stage. The annealing temperature F12 is 150℃ and the annealing time T12 is 30 min to obtain the perovskite light absorption layer.
[0061] (4) The electron transport layer and the perovskite light absorption layer are scribed with a laser to divide the entire functional layer into 98 sub-functional regions. The distance between the P2 line and the P1 line is 0.01 mm and the line width is 0.3 mm.
[0062] (5) Preparation of conductive carbon paste: Polymethyl methacrylate and polyisobutylene are dissolved in a mixed orthogonal solvent of chlorobenzene and xylene at a mass ratio of 5:1 to prepare a polymeric adhesive; 5 μm flake graphite, 20 nm conductive carbon black and multi-walled carbon nanotubes (flake graphite accounts for 80% of the total weight of carbon conductive filler, conductive carbon black accounts for 15% of the total weight of carbon conductive filler, and carbon nanotubes account for 5% of the total weight of carbon conductive filler) are mixed with the polymeric adhesive, and 3% of the total weight of carbon conductive filler nano-sized cuprous thiocyanate powder is added. After vacuum mixing, the mixture is transferred to a three-roll mill with 15°C circulating cooling water and continuously ground 3 times to make the fineness of the conductive carbon paste ≤15 μm, thereby obtaining a conductive carbon paste with good fluidity and uniform dispersion.
[0063] (6) Place the substrate with the functional layer prepared on the screen printing machine platform, adjust the distance between the screen printing stencil and the substrate to 50 mm, and set the screen printing speed V13 = 50 mm / s; uniformly coat the conductive carbon paste onto the nylon stencil, start the screen printing machine platform to directly print the conductive carbon paste onto the exposed perovskite light absorption layer surface, then place it at room temperature for 10 min to release the initial stress, and then immediately anneal it on the hot plate at F14 = 50℃ for 10 min to form a bottom carbon network of about 15 μm thickness; place the substrate on the screen printing machine platform again, replace the nylon stencil with a stainless steel stencil, adjust the distance between the screen printing stencil and the substrate to 50 mm, and set the screen printing speed V14 = 50 mm / s. mm / s; the screen printing platform is started to complete the printing, and then immediately annealed on the hot stage at F15=80℃ for 20min. Finally, a carbon electrode with a total thickness of 50μm and doped with cuprous thiocyanate and without cracking, i.e. the top electrode, is formed on the surface of the bottom carbon network. After laser etching of the carbon electrode, a perovskite solar cell module without a hole layer is obtained.
[0064] Because the inorganic p-type dopant CuSCN particles inside the conductive carbon paste are deposited and anchored in situ within the carbon network system of the carbon conductive filler, the conductive carbon paste can achieve physical contact and electrical interconnection between the carbon electrode and the perovskite phase hole extraction network after low-temperature curing. Moreover, after the CuSCN micro powder is connected to the substrate interface, a three-dimensional bulk phase hole extraction network is formed. This significantly reduces the need for multi-step coating of additional hole transport layers, precious metal evaporation, and high-temperature sintering processes.
[0065] Experiment 2 Multiple hole-free perovskite solar cell units are integrated in series on a glass substrate. The structure of each cell unit, from bottom to top, consists of: a 200nm thick FTO conductive glass substrate, a 100nm thick TiO2 electron transport layer, and an 800nm thick FA layer. 0.6 MA 0.4The system consists of a PbI3 perovskite light-absorbing layer and a 60 μm thick carbon electrode layer containing inorganic p-type dopant, i.e., the top electrode layer. The fabrication methods for each layer are as follows: (1) On a 60×60cm conductive substrate, the surface of the FTO conductive glass substrate is scribed with P1 to form 98 sub-electrode regions.
[0066] (2) Preparation of electron transport layer: Weigh 0.1375 g of bis(2,4-pentanedione)bis(2-propanol)titanium(IV), dissolve it in 2.5 mL of n-butanol to prepare a 0.15 mol / L (acetylacetonate)diisopropyl titanate n-butanol solution; place the FTO conductive glass substrate on the doctor blade platform, adjust the distance between the doctor blade and the substrate to D21 = 0.12 mm, and coat the (acetylacetonate)diisopropyl titanate n-butanol solution on the FTO conductive glass substrate at a doctor blade speed V21 = 12 mm / s. After forming a TiO2 liquid film, immediately transfer it to a hot table for annealing. The annealing temperature is F21 = 450℃ and the time is T21 = 120 min to obtain the TiO2 electron transport layer.
[0067] (3) Preparation of perovskite light-absorbing layer: FAI, MAI and PbI2 are mixed according to FAI... 0.6 MA 0.4 PbI3 was dissolved in DMF solvent according to stoichiometric ratio to prepare a perovskite precursor solution. The substrate with the electron transport layer already coated was placed on the slit coater platform, the coating head gap D22 was set to 0.12 mm, the coating rate V22 was set to 15 mm / s, the perovskite precursor solution was injected and the slit coater platform was started to coat the perovskite precursor solution onto the TiO2 electron transport layer. After forming a perovskite liquid film, it was immediately annealed on a hot stage at a temperature F22 = 150 °C for a time T22 = 30 min to obtain the perovskite light absorption layer.
[0068] (4) The electron transport layer and the perovskite light absorption layer are scribed with a laser to divide the entire functional layer into 98 sub-functional regions. The distance between the P2 line and the P1 line is 0.05 mm and the line width is 0.3 mm.
[0069] (5) Preparation of conductive carbon paste: Polymethyl methacrylate and styrene block copolymer are mixed in toluene orthogonal solvent at a mass ratio of 9:1 to obtain a polymer solution; 5 μm flake graphite, 20 nm conductive carbon black and carbon nanotubes (75% of the total weight of carbon conductive filler, 20% of the total weight of carbon conductive filler and 5% of the total weight of carbon conductive filler) are mixed with the polymer solution, and 5% of the total weight of carbon conductive filler nano-sized nickel oxide powder is added. After vacuum mixing, the mixture is transferred to a three-roll mill with 15℃ circulating cooling water and continuously ground 4 times to make the fineness of the conductive carbon paste ≤15 μm, thereby obtaining a conductive carbon paste with good fluidity and uniform dispersion.
[0070] (6) Place the substrate with the functional layer prepared on the screen printing machine platform, adjust the distance between the screen printing stencil and the substrate to 50 mm, and set the screen printing speed V23 = 50 mm / s; uniformly coat the above conductive carbon paste on the nylon stencil, start the screen printing machine platform to directly print the conductive carbon paste onto the exposed perovskite light absorption layer surface, then place it at room temperature for 10 min to release the initial stress, and then immediately anneal it on the hot stage at F24 = 60℃ for 10 minutes. For min, a bottom carbon network of about 15μm thickness is formed; the substrate is placed on the screen printing machine platform again, the nylon screen is replaced with a stainless steel screen, the distance between the screen printing screen and the substrate is adjusted to 50mm, and the screen printing rate V24 = 50mm / s is set; the screen printing machine platform is started to complete two printings, and after each printing, it is annealed on the hot stage at F25 = 80℃ for 15min, and finally a crack-free carbon electrode with a total thickness of 60μm, i.e., the top electrode, is formed on the surface of the bottom carbon network; after laser etching of the carbon electrode, a perovskite solar cell module without a hole layer is obtained.
[0071] Because the inorganic p-type dopant NiO particles inside the conductive carbon paste are deposited and anchored in situ within the carbon network system of the carbon conductive filler, the conductive carbon paste can achieve physical contact and electrical interconnection between the carbon electrode and the perovskite phase hole extraction network after low-temperature curing. Moreover, after the NiO micro powder is connected to the substrate interface, a three-dimensional bulk phase hole extraction network is formed. This significantly reduces the need for multi-step coating of additional hole transport layers, precious metal evaporation, and high-temperature sintering processes.
[0072] The difference between Experiment 3 and Experiment 1 is that the inorganic p-type semiconductor functional micro powder is cuprous iodide powder, which accounts for 2% of the total mass of the carbon powder. The remaining steps are the same as those in Experiment 1.
[0073] The difference between Experiment 4 and Experiment 1 is that the inorganic p-type semiconductor functional micro powder is tungsten disulfide powder, which accounts for 1% of the total mass of carbon powder. The remaining steps are the same as in Experiment 1.
[0074] The difference between Experiment 5 and Experiment 1 is that the inorganic p-type semiconductor functional micro powder is molybdenum oxide powder, which accounts for 4% of the total mass of the carbon powder. The remaining steps are the same as in Experiment 1.
[0075] The difference between Control Experiment 1 and Experiment 1 is that the conductive carbon paste does not contain inorganic p-type dopants; and the binder is only high molecular weight polystyrene; after the conductive carbon paste is printed on the surface of the exposed perovskite light-absorbing layer, it is directly subjected to high-temperature annealing at 100℃.
[0076] Figure 5 This is a voltage-current diagram after the photoelectric performance test of the perovskite solar cell module in Experiment 1. Figure 6This is a voltage-current diagram after the photoelectric performance test of the perovskite solar cell module in Experiment 2. Figure 7 This is a voltage-current diagram after the photoelectric performance test of the perovskite solar cell module in control experiment 1.
[0077] Table 1. Electrical performance parameters of the perovskite solar cell modules prepared in Experiments 1-5 and Control Experiment 1 Experiment 1 109.0 0.625 0.608 16.08 Experiment 2 109.5 0.625 0.612 16.53 Experiment 3 109.2 0.621 0.605 16.19 Experiment 4 108.8 0.628 0.592 15.96 Experiment 5 108.5 0.622 0.602 15.93 Controlled Experiment 1 99.4 0.616 0.509 12.32 .
[0078] according to Figure 5 , Figure 6 as well as Figure 7 Table 1 shows that, in the embodiments of this application, after integrating carbon paste with inorganic p-type dopant, the perovskite solar cell module in Experiment 2 has the highest hole extraction efficiency. In contrast, Control Experiment 1, which did not use the inorganic p-type dopant integrated conductive carbon paste of this application, has a large interface energy difference and lacks a hole extraction network, resulting in low photoelectric efficiency.
[0079] In other words, the conductive carbon paste of this application can solve the problem of low hole extraction efficiency in hole-free carbon-based perovskite modules, thereby improving the photoelectric conversion efficiency of the device.
[0080] The following is a detailed description of perovskite solar cell modules.
[0081] Please see Figure 3 , Figure 3 This is a schematic diagram of the structure of a perovskite solar cell module according to one embodiment. Figure 3 As shown, the perovskite solar cell module includes: Conductive substrate 301; An electron transport layer 302 is stacked on a conductive substrate 301; A perovskite light-absorbing layer 303 is stacked on the electron transport layer 302; A top electrode layer 304 is stacked on the perovskite light-absorbing layer 303.
[0082] It should be noted that the conductive substrate 301 can be a conductive glass substrate. For example, the conductive substrate 301 can be an ITO conductive glass substrate or an FTO conductive glass substrate. That is to say, the conductive substrate 301 includes a glass substrate 3011 and a conductive layer 3012.
[0083] It should be noted that the conductive substrate 301 can be a conductive glass substrate. For example, the conductive substrate 301 can be an ITO conductive glass substrate or an FTO conductive glass substrate, that is, an ITO conductive layer or an FTO conductive layer is fabricated on the glass substrate.
[0084] It should be noted that the electron transport layer 302 can be formed by coating the mixed dispersion onto the conductive substrate 301 using a slot coating process or a blade coating process, followed by annealing on a hot plate. The mixed dispersion includes either a tin oxide dispersion or a titanium oxide dispersion.
[0085] It should be noted that the perovskite light-absorbing layer 303 can be formed by coating the perovskite solution onto the electron transport layer 302 using a slit coating process, followed by annealing on a hot stage. The perovskite solution includes: FAPbI3 perovskite solution and perovskite precursor solution.
[0086] It should be noted that perovskite solar cell modules do not contain independent organic or inorganic hole transport layers (HTLs). In practical applications, inorganic p-type semiconductor functional powders are low-energy-barrier inorganic p-type semiconductor structures. Their addition mass is arranged in a multi-level manner based on the viscosity of the conductive carbon paste system and the quantity of carbon conductive filler, ensuring that each carbon network loop in the carbon network system of the carbon conductive filler is covered by a large number of dispersed inorganic p-type semiconductor functional powders. Because the inorganic p-type semiconductor functional powders are embedded in situ within the conductive carbon paste, they are simultaneously coated by the conductive carbon paste during the printing and molding of the top electrode layer (304). The cured carbon material and the inorganic p-type semiconductor functional powders achieve electrical interconnection and physical anchoring, forming an integrated structure without an external hole transport layer. Thus, in the absence of an independent hole layer or under conditions of energy level mismatch, holes at the carbon / perovskite interface can be rapidly extracted, suppressing carrier recombination effects, while also significantly reducing coating steps and sintering processes.
[0087] In some embodiments, the top electrode layer 304 is formed by coating the exposed perovskite light-absorbing layer 303 with the above-mentioned conductive carbon paste and then drying and curing it at low temperature to form a three-dimensional bulk hole extraction network.
[0088] It should be noted that the low-temperature drying and curing temperature is between 50℃ and 150℃. That is, after coating the exposed perovskite light-absorbing layer 303 with conductive carbon paste, it is dried and cured at an environment of 50℃ to 150℃ to form a three-dimensional bulk hole extraction network. It should be noted that the drying and curing temperature of the conductive carbon paste can be any temperature between 50℃ and 150℃; for example, the drying and curing temperature of the conductive carbon paste can be 50℃, 65℃, 83℃, 100℃, 120℃, or 150℃.
[0089] It should be noted that the conductive carbon paste can be applied by scraping or screen printing.
[0090] It should be noted that the scraping method and screen printing are existing printing processes, and will not be elaborated on here.
[0091] Figure 4 This is a scanning electron microscope (SEM) image of the top electrode of the perovskite solar cell module from Experiment 2. From... Figure 4 As can be seen, the SEM image of the carbon electrode, magnified 10,000 times (scale bar 1 μm), shows that the carbon nanoparticles are fine, flocculent, and nano-sized particles, and are evenly distributed. A large number of carbon particles are stacked and aggregated to form a dense structure. At the same time, a small number of large, sheet-like conductive graphite particles are also visible mixed in. This multi-scale material structure is more conducive to charge transport because a three-dimensional bulk hole extraction network is constructed inside the top electrode layer 304. Compared with the traditional two-dimensional planar independent hole layer, this three-dimensional bulk hole extraction network greatly shortens the charge transport distance, significantly reduces the contact resistance, and greatly improves the open-circuit voltage and fill factor of the hole-free battery. That is, it greatly improves the charge separation efficiency of the carbon / perovskite interface, thus completely eliminating the expensive and easily degradable independent hole transport layer in the traditional battery structure.
[0092] The non-crystalline polyolefin elastomer of this application is integrated within the structure of a thermoplastic binder, located between the carbon conductive filler and the perovskite substrate, and forms an integrated encapsulation network with the polar polyester film to reduce the synergistic erosion of the carbon layer structure and the sub-cells of the battery module by environmental moisture, oxygen, and thermal shrinkage stress. The carbon conductive filler of this application adopts a multi-level particle ratio structure, ensuring that the maximum volume shrinkage rate of each coating segment during drying does not exceed the safety threshold, thereby significantly reducing the local physical stress and cracking risk of the top electrode layer. During the printing and molding of the top electrode layer, inorganic p-type semiconductor functional micropowder is simultaneously and in-situ embedded in the carbon conductive network of the carbon conductive filler. Within the network system or bulk contact network, after gradient low-temperature co-curing, carbon materials and inorganic p-type semiconductor functional microparticles complete electrical interconnection and physical anchoring, realizing non-destructive electrical interconnection and integrated physical encapsulation of a three-dimensional bulk hole extraction network and electrodes. This eliminates the need for additional hole layer coating, noble metal evaporation, and high-temperature sintering processes. This three-dimensional bulk hole extraction network can conduct hole current when charge separation occurs at the carbon / perovskite interface, thereby suppressing the generation of carrier recombination effect. The conductive carbon paste of this application achieves non-destructive electrical connection with the perovskite light absorption layer through screen printing, thus being compatible with low-temperature, fully printed, and flexible fabrication processes.
[0093] In one implementation of this application, an optoelectronic device is also provided, which includes a perovskite solar cell module employing the aforementioned conductive carbon paste.
[0094] The optoelectronic device of this application uses a hole-free perovskite solar cell module constructed with the aforementioned conductive carbon paste. Because the conductive carbon paste has extremely high crack resistance and excellent non-destructive stability to the perovskite layer, the optoelectronic device constructed with the perovskite solar cell module using the aforementioned conductive carbon paste also has higher stability and longer service life.
[0095] In some embodiments, the specific forms of photovoltaic devices may include solar streetlights, LED lights, solar chargers, solar panels, solar water heaters, solar power generation systems, etc. These devices utilize and store solar energy by converting solar energy into electrical energy.
[0096] This document describes various exemplary embodiments with reference to them. However, those skilled in the art will recognize that changes and modifications can be made to the exemplary embodiments without departing from the scope of this document. For example, various operational steps and components for performing operational steps can be implemented in different ways depending on the specific application or considering any number of cost functions associated with the operation of the system (e.g., one or more steps can be deleted, modified, or combined with other steps).
[0097] While the principles herein have been illustrated in various embodiments, numerous modifications to the structures, arrangements, proportions, elements, materials, and components, particularly suited to specific environments and operational requirements, may be used without departing from the principles and scope of this disclosure. These modifications and other alterations or alterations will be included within the scope of this document. Those skilled in the art will recognize that many changes can be made to the details of the above embodiments without departing from the fundamental principles of the invention.
Claims
1. A conductive carbon paste, characterized in that, include: Orthogonal nonpolar solvents, thermoplastic binders, carbon conductive fillers, and inorganic p-type semiconductor functional micropowders.
2. The conductive carbon paste as described in claim 1, characterized in that, The thermoplastic binder accounts for 10% to 50% of the total solids content of the conductive carbon paste; the carbon conductive filler accounts for 50% to 90% of the total solids content of the conductive carbon paste.
3. The conductive carbon paste as described in claim 1, characterized in that, The orthogonal nonpolar solvent includes low-boiling-point solvents and high-boiling-point solvents; the low-boiling-point solvent includes at least one of ethyl acetate, methyl acetate, propyl acetate, and naphtha; the high-boiling-point solvent includes at least one of chlorobenzene, toluene, xylene, anisole, terpineol, isooctyl alcohol, aromatic 150, aromatic 100, propylene glycol methyl ether acetate, dipropylene glycol monomethyl ether, diacetone alcohol, ethylene glycol ethyl ether acetate, diethylene glycol ethyl ether acetate, and propylene glycol methyl ether acetate.
4. The conductive carbon paste as described in claim 1, characterized in that, The thermoplastic binder comprises: a polar ester-based polymer and an amorphous polyolefin elastomer, wherein the mass ratio of the polar ester-based polymer to the amorphous polyolefin elastomer is 5:1 to 9:1; the polar ester-based polymer includes polymethyl methacrylate; and the amorphous polyolefin elastomer includes polyisobutylene or styrene block copolymer.
5. The conductive carbon paste as described in claim 1, characterized in that, The carbon conductive filler includes: micron-sized flake graphite, nano-sized conductive carbon black, nano-sized Ketjen black, and one-dimensional carbon nanotubes; the carbon conductive filler is composed of micron-sized flake graphite, nano-sized conductive carbon black, and one-dimensional carbon nanotubes; the micron-sized flake graphite accounts for 50% to 80% of the total weight of the carbon conductive filler, the nano-sized conductive carbon black accounts for 10% to 40% of the total weight of the carbon conductive filler, the nano-sized Ketjen black accounts for 5% to 10% of the total weight of the carbon conductive filler, and the one-dimensional carbon nanotubes account for 5% to 10% of the total weight of the carbon conductive filler.
6. The conductive carbon paste as described in claim 1, characterized in that, The inorganic p-type semiconductor functional micro powder includes at least one of cuprous thiocyanate, nickel oxide, molybdenum disulfide, tungsten disulfide, cuprous oxide, cuprous iodide, and molybdenum oxide micro powder; the average particle size of the inorganic p-type semiconductor functional micro powder is between 10 nm and 500 nm; the inorganic p-type semiconductor functional micro powder accounts for 0.5% to 20% of the total weight of the carbon conductive filler.
7. The method for preparing conductive carbon paste according to any one of claims 1-6, characterized in that, The method includes: A thermoplastic adhesive is dissolved in an orthogonal nonpolar solvent to obtain a polymeric adhesive solution. Carbon conductive filler, inorganic p-type semiconductor functional micro powder and the polymer adhesive are mixed to fully wet and coat the solid powder to obtain a coarse slurry. The coarse slurry is sheared and ground to uniformly anchor the inorganic p-type semiconductor functional micro powder in situ within the carbon network system of the carbon conductive filler, thereby obtaining the conductive carbon slurry.
8. The preparation method according to claim 7, characterized in that, The fineness of the conductive carbon paste is less than or equal to 15 μm.
9. A perovskite solar cell module, characterized in that, include: Conductive substrate; An electron transport layer is stacked on the conductive substrate; A perovskite light-absorbing layer is stacked on the electron transport layer; A top electrode layer is stacked on the perovskite light-absorbing layer.
10. The perovskite solar cell module as described in claim 9, characterized in that, The top electrode layer is formed by coating the exposed perovskite light absorption layer surface with the conductive carbon paste as described in any one of claims 1-6, and then drying and curing it at low temperature to form a three-dimensional bulk hole extraction network.